2008
DOI: 10.1007/s11368-008-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the membrane interphase probe (MIP): an evaluation

Abstract: Background, aim, and scope The membrane interphase probe (MIP™) from Geoprobe Systems® has frequently been applied in different countries for the characterization of soil contaminated with volatile organic carbons (VOCs). Experience shows that misinterpretation of the collected data is common. This is mainly due to the lack of understanding and knowledge related to the detectors used, their detection limits, and the sensitivity of the MIP system. It has been noticed that the sensitivity of the system given by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…In areas where concentrations are lower (down to about 0.1 mg/kg), the ECD was more useful because of its greater sensitivity to PCE and TCE and therefore lower detection limits. These detection limits are similar to those cited by Ravella et al () for the MIP ECD (200 µg/L PCE or TCE) but lower than those cited by Bronders et al () for the MIP PID (10 mg/L TCE, 50 mg/L PCE).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In areas where concentrations are lower (down to about 0.1 mg/kg), the ECD was more useful because of its greater sensitivity to PCE and TCE and therefore lower detection limits. These detection limits are similar to those cited by Ravella et al () for the MIP ECD (200 µg/L PCE or TCE) but lower than those cited by Bronders et al () for the MIP PID (10 mg/L TCE, 50 mg/L PCE).…”
Section: Discussionsupporting
confidence: 88%
“…(2) "Standard" is based on standard protocol for MIP use detailed by ASTM (2012) and/or the baseline value used as part of this project (see Tables 1 and 2). PCE or TCE) but lower than those cited by Bronders et al (2009) for the MIP PID (10 mg/L TCE, 50 mg/L PCE). The disparity in ECD response to compounds having two chlorine atoms (i.e., cis-1,2-DCE) vs. compounds having three or more chlorine atoms (i.e., TCE and PCE) likely introduced variability and complicated data interpretation.…”
Section: Detector Utilitymentioning
confidence: 56%
“…This method allows the measurement of the distribution of hydrogeological, geotechnical and geophysical properties along a vertical profile by advancing small probes into the subsurface (Lessoff et al, 2010;Schulmeister et al, 2003). It is also applicable for the highly resolved characterization of contamination patterns and for delineation of contaminant source areas and plumes by direct sampling (Rein et al, 2011) or by indirect methods, for example, by screening for volatile organic compounds (Bronders et al, 2009). Though the minimally invasive direct push technology is comparably time and cost efficient, a large number of soundings is often necessary to reliably characterize contaminated sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, experience gathered from field and laboratory testing has indicated that the application of this system (and therefore interpretation and assessment of measured results) is not always straightforward (Bronders et al 2009). Often results are misinterpreted, for example, when attempting to quantify concentrations of contaminants in the soil or groundwater.…”
Section: Introductionmentioning
confidence: 99%